3′-Geranyl-mono-substituted chalcone Xanthoangelovl induces apoptosis in human leukemia K562 cells via activation of mitochondrial pathway. (5th January 2017) - Teng, Yuou; Wang, Lixin; Liu, Huan; Yuan, Yuan; Zhang, Qian; Wu, Meng; Wang, Luyao; Wang, Haomeng; Liu, Zhen; Yu, Peng
Abstract: 3′-Geranyl-mono-substituted chalcone Xanthoangelol (1b ), a chalcone derivative, was previously reported to show selective cytotoxicity against human chronic myelogenous leukemia K562 cells with a half-maximal inhibitory concentration (IC50 ) of 3.98 μM. In the present study, we investigated the molecular mechanism underlying the cytotoxicity of1b in K562 cells. Treatment with compound1b caused K562 cells to adopt a typical apoptotic morphology. Flow cytometric analysis also confirmed the presence of an apoptotic cell population following treatment of Annexin-V-FITC and propidium iodide (PI) double-labeled K562 cells with1b . Furthermore, we observed dissipation of the mitochondrial membrane potential, caspase-3 activation, and a reduction of the Bcl-2/Bax ratio in these cells, which suggest that the mitochondrial apoptotic pathway is induced by1b in K562 cells. Collectively, our findings demonstrate that compound1b notably induces mitochondrial-mediated apoptosis in K562 cells, which might have a potential anticancer activity. Highlights: 3′-Geranyl-mono-substituted chalcone Xanthoangelol (1b) had potent cytotoxicity. Compound 1b affects the mitochondrial functions. Compound 1b inhibits K562 cell proliferation via mitochondria-mediated apoptosis.